The Impact of the Built Environment on Students' Social and Cultural Sustainability in Educational Campuses: Istanbul Okan University Case - Madaki DUNAMA; Eda ÖZSOY (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
It is common knowledge that well-functioning buildings improve our lives, communities, and culture. This paper describes the intricate relationship between architecture, spatial design, and the sustainable well-being of educational institutions. How physical spaces impact social interactions, foster cultural exchange, and contribute to long-term sustainability is explored. Social sustainability, which aims to define, organize, and develop social life based on humans and their relationships/interactions in social life, requires a versatile and well-understood relationship between the built environment and society. By combining qualitative research, user surveys, and architectural analysis, this paper provides actionable insights for enhancing the social and cultural sustainability of educational campuses.It is extremely important to evaluate the spatial quality of the built environment in terms of students' sense of belonging, social ties, sense of community, trust, and physical well-being when using university campuses for students coming from different cultures, different cities/countries, and different professions. This study, which will focus on Istanbul Okan University Campus as a case study, will propose an original evaluation framework that relates the functional quality of the campus’s-built environment to various spatial qualities at different spatial levels for evaluating social sustainability in campus life.